Attempted synthesis of central furopyran core of diocollettines A via a gold-catalyzed cascade 1,6-diyne cycloisomerization process - Mullapudi, Venkannababu; Ramana, V, Chepuri (Tetrahedron Letters, 2020)
Herein, we describe an Au-catalyzed cascade diyne cycloisomerization process that was projected to construct the central furopyran bicyclic core of Diocollettines A. Our intended strategy for the annulation of the third thf ring is based on epoxidation and subsequent intramolecular acetalization. However, the initial alkynol cyclization occurred in an undesired 5-exo-dig mode, ultimately leading to an undesired furopyran. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: 1; 6-Hexadiyne; Alkynol cycloisomerization; Diocollettines A; Gold-catalysis; Total synthesis

Discovery of 3-(benzofuran-2-ylmethyl)-1H-indole derivatives as potential autophagy inducers in cervical cancer cells - Siddiqui, Shaziyaparveen K.; SahayaSheela, Vinodh J.; Kolluru, Srinivas; Pandian, Ganesh N.; Santhoshkumar, Thankayyan R.; Dan, Vipin M.; Ramana, V, Chepuri (Bioorganic & Medicinal Chemistry Letters, 2020)
In this manuscript we have documented the identification of a novel anticancer scaffold 3-(benzofuran-2-yl-methyl)-1H-indole. This scaffold has been designed by tweaking the known bisindolylmethane scaffold of natural products that display a wide range of biological activities. A series of 24 new conjugates have been synthesized and among them 5 derivatives exhibited IC50 values less than 40 mu M against two cervical cancer cell lines SiHa and C33a. Further mechanistic studies of two compounds 3eb and 3ec revealed that the toxicity of these compounds was due to the effective induction of autophagy mediated cell death. The autophagy induction was confirmed by the progressive conversion of LC3I to LC3II and downregulation of p62 in cervical cancer cells.
Keywords: Autophagy; Benzofuran; Bisindolylmethane; Cervical cancer; Friedel-Crafts alkylation

NADP-dependent glutamate dehydrogenases in a dimorphic zygomycete Benjaminiella poitrasii: purification, characterization and their evaluation as an antifungal drug target - Pathan, Ejaj K.; Kulkarni, Anand M.; Prasanna, Nallaballe V. L.; Ramana, V, Chepuri; Deshpande, V, Mukund (Biochimica Et Biophysica Acta-General Subjects, 2020)
Background: It has been reported that the genes coding for NADP-dependent glutamate dehydrogenases (NADP-GDHs) showed a cause-effect relationship with Yeast-Hypha (Y-H) reversible transition in a zygomycete Benjaminiella poitrasii. As Y-H transition is significant in human pathogenic fungi for their survival and proliferation in the host, the NADP-GDHs can be explored as antifungal drug targets. Methods: The yeast-form specific BpNADPGDH I and hyphal-form specific BpNADPGDH II of B. poitrasii were purified by heterologous expression in E. coll. BL-21 cells and characterized. The structural analogs of L-glutamate, dimethyl esters of isophthalic acid (DMIP) and its derivatives were designed, synthesized and screened for inhibition of NADP-GDH activity as well as Y-H transition in B. poitrasii, and also in human pathogenic Candida albicans strains. Results: The BpNADPGDH I and BpNADPGDH II were found to be homo-hexameric proteins with native molecular mass of 282 kDa and 298 kDa, respectively and subunit molecular weights of 47 kDa and 49 kDa, respectively. Besides the distinct kinetic properties, BpNADPGDH I and BpNADPGDH II were found to be regulated by cAMP-dependent- and Calmodulin (CaM) dependent- protein kinases, respectively. The DMIP compounds showed a more pronounced effect on H-form specific BpNADPGDH II and inhibited Y-H transition as well as growth in B. poitrasii and C. albicans strains. Conclusion: The present study will be useful to design and develop antifungal drugs against dimorphic human pathogens using glutamate dehydrogenase as a target. Significance: Glutamate dehydrogenases can be explored as a target against human pathogenic fungi.
Keywords: Antifungal compound; Benjaminiella poitrasii; Candida albicans; Dimethyl esters and amides of isophthalic acid; dimorphism; Enzyme inhibition; NADP-glutamate dehydrogenases

Total synthesis of (+)-petromyroxol, (-)-iso-petromyroxol, and possible diastereomers - Mullapudi, Venkannababu; Ahmad, Iram; Senapati, Sibadatta; Ramana, V, Chepuri (ACS Omega, 2020)
The total synthesis of (+)-petromyroxol (1) and its seven diastereomers including the ()-tso-petromyroxol (2) is described. The employed strategy involves the use of easily available CS-epimeric epoxides 5 and 5' and nonselective anomeric C1-allylation, proceeding with or without inversion at C2 thereby giving the possibility of synthesizing all possible diastereomers. Extensive two-dimensional (2D) NMR analyses of all eight diastereomers have been carried out to assign the chemical shifts of the central carbons land the corresponding attached hydrogens and to learn how the C/H-chemical shifts of the tetrahydrofuran ring were influenced by the adjacent centers.

Concise/catalytic approach for the construction of the C14-C28 fragment of eribulin - Senapati, Sibadatta; Ramana, V, Chepuri (Organic & Biomolecular Chemistry, 2021)
A simple approach for the synthesis of the C14-C28 fragment of eribulin has been developed by employing a one-pot gold-catalyzed alkynol cyclization/Kishi reduction to construct the 1,5-cis-tetrahydropyran unit and a cross-metathesis/Sharpless asymmetric dihydroxylation-cycloetherification to install the 1,4-trans-tetrahydrofuran ring. Use of easily accessible building blocks, ease of operation and catalytic transformations as key reactions for the construction of THF/THP units highlight the current approach.

Intermolecular interception of alpha-oxo gold carbenes of nitroalkyne cycloisomerization with 1, 2-benzo[d]isoxazole: synthesis of functionalized quinazoline 1-oxides - Dhote, Pawan S.; Pund, Kishor A.; Ramana, V, Chepuri (Journal of Organic Chemistry, 2021)
The known nitrogen-transfer reagent 1,2-benzo[d]isoxazole has been used to trap the postulated a-oxo gold carbene intermediate involved in the [Au]-catalyzed internal redox process of 2-alkynylnitrobenzenes. This process led us to develop a general convergent method for the synthesis of highly functionalized quinazoline 1-oxides.

Interrupting the [Au]-catalyzed nitroalkyne cycloisomerization: trapping the putative alpha-oxo gold carbene with benzo[c]isoxazole - Dhote, Pawan S.; Ramana, V, Chepuri (Organic Letters, 2021)
The [Au]-catalyzed nitroalkyne cycloisomerization of 2-alkynylnitrobenzenes leading to anthranils has been interrupted by possible trapping of the postulated intermediate alpha-oxo gold carbene with an external nucleophile such as benzo[c]isoxazole (anthranil). At the outset, this provides a simple synthesis of highly functionalized 3-acyl-(2-formylphenyl)-2H-indazoles with the sequential C-O, C-N, and N-N bond formations. This provides indirect support for the existence of alpha-oxo gold carbenes in the [Au]-catalyzed internal redox processes of nitroalkynes.

Synthesis of anisotropic rod-like gold nanostructures in organic media - Prasad, V, Bhagavatula L.; Sivasankaran, Prathap Chandran; Patel, Pitambar; Malekar, V, Pushpa; Maya, V, K.; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
Synthesis of anisotropic rod-like gold nanostructures was carried out in chloroform employing a modified ascorbic acid derivative as a reducing agent in the presence and absence of seed particles. The seed particles and/or the chloroaurate ions were phase transferred to the organic media using n-octadecyl amine. High-resolution transmission electron microscopy analysis clearly revealed that the anisotropic structures are single crystalline in nature. The stabilization of certain crystallographic faces of anisotropic gold nanostructures by amines is invoked to explain the formation of these structures.

Synthesis of four diastereomers of notoryne and their C-13 NMR chemical shifts analysis - Senapati, Sibadatta; Das, Shyamsundar; Dixit, Ruchi; Vanka, Kumar; Ramana, V, Chepuri (Journal of Chemical Sciences, 2021)
In this manuscript we document the details of the synthesis of four diastereomers of notoryne. The synthesis of one of the diastereomer having a similar relative stereochemistry of substituents on the both THF rings like notoryne, however, being the relative stereochemistry between the bridging carbon of these two THF units is changed from anti to syn has been executed mainly to learn how the ring carbon chemical shifts vary with this change. Interestingly, the deviations are found mainly for the carbons of THF ring that bears the Br-group. In addition to this isomer, three more diastereomers having the relative stereochemistry of substituents on either of the THF rings varied have been also synthesized. All four diastereomers have been subjected for extensive NMR studies and their C-13 NMR chemical shifts have been compared with notoryne and laurendecumenyne B. In addition, chemical shifts for the four diastereomers along with these natural products were calculated with the help of DFT calculations and compared to the experimentally obtained chemical shift values.